2015
DOI: 10.2139/ssrn.2553076
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Out of Poverty Traps: Internal Migration and Interregional Convergence in Russia

Abstract: Guriev, Sergei, and Vakulenko, Elena-Breaking out of poverty traps: Internal migration and interregional convergence in RussiaWe study barriers to labor mobility using panel data on gross region-to-region migration flows in Russia in 1996-2010. Using both parametric and semiparametric methods and controlling for region-to-region pairwise fixed effects, we find a non-monotonic relation-ship between income and migration. In richer regions, higher incomes result in lower migration outflows. However, in the poores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 14 publications
2
32
0
5
Order By: Relevance
“…Concerning Russia, this phenomenon was prevalent during the recession of the 1990s, when potential migrants were frequently unable to finance their migration plans (Andrienko and Guriev ). This problem, however, was largely eliminated through the 2000s (Guriev and Vakulenko ).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning Russia, this phenomenon was prevalent during the recession of the 1990s, when potential migrants were frequently unable to finance their migration plans (Andrienko and Guriev ). This problem, however, was largely eliminated through the 2000s (Guriev and Vakulenko ).…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, distances among Brazil, Russia, and China will disappear, to make a pool of competitors. Global development of stock markets has allowed even the less-developed Russian regions to improve and ameliorate poverty [57], while the economic growth expectations in the Brazilian case will continue slowly, and growth from China relies on intensive diplomatic commercial dealings with the US [56].…”
Section: Complete Estimation Of Gdp Per Capitamentioning
confidence: 99%
“…In the case of China, that would mean relaxing the Hukou household registration system. A recent study of Russia, for the period 1995-2010, found that when barriers that hindered internal labour migration in the 1990s were eliminated, the economies of the poorer Russian regions grew out of their poverty trap and their income levels converged toward those in moreaffluent Russian regions in the first decade of this century (Guriev and Vakulenko 2015). Reducing such barriers to worker movements would increase the payoff from boosting the above-mentioned under-investments in rural education, health and infrastructure too.…”
Section: Freeing Up Factor Marketsmentioning
confidence: 99%